Correlates of personal health record registration and utilization among veterans with HIV. Issue 2 (16th June 2021) - Avoundjian, Tigran; Troszak, Lara; Cave, Shayna; Shimada, Stephanie; McInnes, Keith; Midboe, Amanda M
Abstract: Objective: We examined correlates of registration and utilization of the Veteran Health Administration's (VHA) personal health record (PHR), My HealtheVet (MHV), among a national cohort of veterans living with HIV. Materials and Methods: Using VHA administrative data, we matched veterans with HIV who registered for MHV in fiscal year 2012–2018 ( n = 8589) to 8589 veterans with HIV who did not register for MHV. We compared demographic and geographic characteristics, housing status, comorbidities, and non-VHA care between MHV registrants and nonregistrants to identify correlates of MHV registration. Among registrants, we examined the association between these characteristics and MHV tool use (prescription refill, record download, secure messaging, view labs, and view appointments). Results: MHV registrants were more likely to be younger, women, White, and to have bipolar disorder, depression, or post-traumatic stress disorder diagnosis than nonregistrants. Having a substance use disorder (SUD) diagnosis or a higher Elixhauser score was associated with lower odds of MHV registration. Among registrants, women were less likely to use prescription refill. Patients who were at risk of homelessness in the past year were less likely to use secure messaging and, along with those who were homeless, were less likely to use view labs and prescription refill. Bipolar disorder and depression were associated with increased secure messaging use. Diagnoses of SUD and alcohol use disorder were both associated with lower rates of prescription refill. Discussion: Among veterans living with HIV, we identified significant differences in PHR registration and utilization by race, sex, age, housing status, and diagnosis.